The potential links between human gut microbiota and cardiovascular health and disease - is there a gut-cardiovascular axis? - Almeida, Cátia; Gonçalves-Nobre, J. Guilherme; Alpuim Costa, Diogo; Barata, Pedro (Frontiers in Gastroenterology, 2023)
The gut-heart axis is an emerging concept highlighting the crucial link between gut microbiota and cardiovascular diseases (CVDs). Recent studies have demonstrated that gut microbiota is pivotal in regulating host metabolism, inflammation, and immune function, critical drivers of CVD pathophysiology. Despite a strong link between gut microbiota and CVDs, this ecosystem's complexity still needs to be fully understood. The short-chain fatty acids, trimethylamine N-oxide, bile acids, and polyamines are directly or indirectly involved in the development and prognosis of CVDs. This review explores the relationship between gut microbiota metabolites and CVDs, focusing on atherosclerosis and hypertension, and analyzes personalized microbiota-based modulation interventions, such as physical activity, diet, probiotics, prebiotics, and fecal microbiota transplantation, as a promising strategy for CVD prevention and treatment.